Fashion and the Politics of the Body: Resistance among Young Feminist Activists in Yogyakarta - Bagus Ajy Waskyto Sugiyanto (MUWAZAH : jurnal kajian gender, 2026)
This study will examine fashion as a form of resistance for women to actualize bodily autonomy. Women's lives within a patriarchal system shape the formation of a controlled discourse on women's fashion. This study interprets this control over women's fashion as a process of domesticating the body (docile bodies). Sandra Lee emphasizes that women's bodies are subject to discriminatory control. However, counter-discourse can change hegemonic discourse through the circulation of what Foucault calls "subjugated knowledge.” Therefore, this study aims to examine fashion as a site of counter-discourse about what fashion means to young female feminist activists who refuse to contribute to the production of the discourse of "domesticated bodies." This study observes young female feminist activists in the Special Region of Yogyakarta. It is qualitative research. Data collection techniques include three methods: observation, interviews, and literature review. This study utilized interviews with several young female feminist activists in the Special Region of Yogyakarta. The selection of informants used purposive sampling techniques, with a background as a student (either state or private in DIY) and involvement in the feminist activism movement. The results of the study show the following counter-discourse: first, a new awareness that the body is a space for contestation of resistance; second, the informants show new fashion expressions, which are autonomous choices for their bodies; and third, using fashion as a means to spread their freedom and spread feminist issues.